“Revista-Valise”: from its creation to its editing experience - Kern, Daniela; Cezar, Claudia Zimmer de Cerqueira; Gassen, Fernanda Bulegon; Sacco, Helene Gomes; Polidoro, Marina Bortoluz; Araújo, Viviane Gil (PORTO ARTE: Revista de Artes Visuais, 2013)
This article aims to convey the reflections implemented throughout the preparation process of “Revista-Valise”, as well as its development and creation experience. “Revista-Valise” is a biannual visual arts-oriented academic journal managed by the alumni at Federal University of Rio Grande do Sul (UFRGS)’s Graduate Program in Visual Arts. Here, we will present all the steps taken to build it, such as the project’s goals, the editorial team’s formation, the delineation of the journal’s scope, tutorials, invitation of peers, editals and details on receiving and forwarding articles to peers for evaluation.